High-flame-retardant new energy cable material and preparation method thereof
Patent Information
- Application Number
- CN202510073818.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
Smart Images

Figure CN119823510A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cable materials, in particular to a highly flame-retardant new energy cable material and a preparation method thereof. Background Art
[0002] New energy cables refer to cables specially designed for new energy fields such as solar energy, wind energy, electric vehicles, etc. These cables usually need to have high temperature resistance, cold resistance, UV resistance, oil resistance, chemical corrosion resistance, aging resistance and other characteristics to meet the requirements of different new energy application environments. New energy cables are mainly composed of conductors, conductor shielding layers, insulation layers, insulation shielding layers, buffer layers, metal sheaths, outer sheaths, etc. Among them, most of the outer sheaths are located in the outermost layer of the cable to protect the cable. Currently, plastics, rubber, etc. are mostly used as the main materials.
[0003] During the use of current flame-retardant cables, in order to achieve high flame-retardant properties, a large amount of flame retardants are often added, which may lead to a decrease in the mechanical strength of the material. For example, the tensile strength, tear strength, and wear resistance are not as good as traditional cable materials. At the same time, in order to ensure high flame retardancy, the flexibility of the cable is also insufficient. Although the insulation resistance and voltage resistance of high flame-retardant cable materials can usually meet general requirements, under certain extreme conditions, such as long-term work in high temperature and high humidity environments, the insulation layer may gradually age, resulting in a decrease in electrical performance. Summary of the invention
[0004] The object of the present invention is to provide a highly flame-retardant new energy cable material and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above-mentioned purpose, the first part of the present invention provides the following technical scheme, a highly flame-retardant new energy cable material, which comprises the following component raw materials by weight: 100-130 parts of polyvinyl chloride, 30-40 parts of ethylene-vinyl acetate copolymer, 15-20 parts of modified ammonium polyphosphate, 10-15 parts of melamine cyanurate, 5-10 parts of nano-montmorillonite, 8-12 parts of mica powder, 5-8 parts of silane coupling agent modified nano-silica, 3-5 parts of bio-based degradable polyester fiber, and 5-15 parts of auxiliary additives.
[0006] In a further embodiment, the new energy cable material is made of the following component raw materials in parts by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of modified ammonium polyphosphate, 13 parts of melamine cyanurate, 8 parts of nano-montmorillonite, 9 parts of mica powder, 6 parts of silane coupling agent modified nano-silica, 4 parts of bio-based degradable polyester fiber, and 10 parts of auxiliary additives.
[0007] In a further embodiment, the modified ammonium polyphosphate is a mixture of melamine-formaldehyde resin, urea-formaldehyde resin and gelatin-gum arabic in a mass ratio of 5:3:2; The auxiliary additives include: plasticizer, compatibilizer, antioxidant and light stabilizer; Wherein, the plasticizer is dioctyl phthalate, the compatibilizer is maleic anhydride grafted polyethylene, the antioxidant is a hindered phenol antioxidant, and the light stabilizer is a hindered amine light stabilizer.
[0008] In a further embodiment, the preparation method of the modified ammonium polyphosphate is as follows: 1) Selecting ammonium polyphosphate particles as raw materials, and then preparing a corresponding amount of ethanol solution and a container, then adding the ammonium polyphosphate particles and the ethanol solution into the container, and simultaneously adding a dispersant, and then starting stirring to obtain an ammonium polyphosphate suspension; 2) Prepare another container, add melamine-formaldehyde resin, urea-formaldehyde resin and gelatin-arabic gum into the container, add a corresponding amount of clean water, start stirring until mixing is complete, and obtain a prepolymer solution; 3) Add the ammonium polyphosphate suspension to the prepolymer solution, stir and mix again, and allow the mixture to stand for reaction after the mixture is mixed. After the reaction is completed, filter, wash and dry the modified ammonium polyphosphate mixture to obtain modified ammonium polyphosphate particles.
[0009] In a further embodiment, the static reaction time of the ammonium polyphosphate suspension and the prepolymer solution after stirring and mixing is 5-10 hours, and the modified ammonium polyphosphate mixed solution is dried by vacuum freeze drying.
[0010] In a further embodiment, the pH value of the prepolymer solution is acidic, specifically, the pH value is 3-5, and the preparation reaction temperature of the prepolymer solution is 60-85°C.
[0011] The second part of the present invention provides the following technical solution, the preparation method of the highly flame-retardant new energy cable material is applied to any of the highly flame-retardant new energy cable materials described, characterized in that the preparation method of the new energy cable material is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry.
[0012] 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed.
[0013] 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating to ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, plasticize the polyvinyl chloride and ethylene-vinyl acetate copolymer for 5 to 8 minutes until they are melted and softened to form the base material raw material of the new energy cable material.
[0014] 4) Then, add nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives into the internal mixer in order. Then, adjust the temperature of the internal mixer to 130-150°C and continue mixing for 20-30 minutes to form a masterbatch of new energy cable materials.
[0015] 5) Adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally kneaded mixture.
[0016] 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained.
[0017] In a further embodiment, the extruder is divided into three parts, namely zone one, zone two and zone three, and the temperature settings of each zone of the extruder are: zone one 150-170°C, zone two 170-190°C, zone three 190-210°C.
[0018] In a further embodiment, the extrusion screw speed in the extruder is 90-130 rpm.
[0019] In a further embodiment, the pretreatment method of polyvinyl chloride and ethylene-vinyl acetate copolymer is as follows: 1) Prepare a stainless steel container, pour polyvinyl chloride and ethylene-vinyl acetate copolymer into the stainless steel container, and spread the polyvinyl chloride and ethylene-vinyl acetate copolymer evenly; 2) Then put the stainless steel container containing polyvinyl chloride and ethylene-vinyl acetate copolymer into the vacuum oven, then start the vacuum oven, set the drying temperature to 40-60°C, and then perform vacuum extraction to reduce the vacuum degree in the vacuum oven to 0.09-0.1MPa, and the drying time is 3-5h; 3) After the vacuum drying of polyvinyl chloride and ethylene-vinyl acetate copolymer is completed, the vacuum oven is closed and nitrogen is filled into the vacuum oven until the pressure in the vacuum oven returns to normal pressure, and then the polyvinyl chloride and ethylene-vinyl acetate copolymer are taken out to complete the pretreatment of polyvinyl chloride and ethylene-vinyl acetate copolymer.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adds modified ammonium polyphosphate, which is an inorganic high-efficiency flame retardant. It decomposes at high temperature to produce non-combustible gases such as phosphoric acid and ammonia. On the one hand, it dilutes the concentration of combustible gas and reduces the possibility of combustion. On the other hand, phosphoric acid can promote the dehydration and carbonization of the material surface to form a heat-insulating and oxygen-isolating carbon layer, which effectively prevents the spread of flames. At the same time, melamine cyanurate and nano-montmorillonite are added. One of them decomposes and absorbs heat when heated, releasing inert gases such as nitrogen and ammonia, playing a dual role of diluting combustible gas and cooling and flame retardant. Secondly, it can participate in the flame retardant process, and assist in improving the flame retardant effect of the above-mentioned materials by adsorbing free radicals generated by combustion, thereby improving the flame retardant performance of the new energy cable; 2. In the present invention, nano-montmorillonite is a natural layered silicate clay mineral. After nano-level processing, it has a large specific surface area. Its lamellar structure can play a physical strengthening role in the material, just like a tiny "rebar", which improves the overall mechanical strength of the material and enables the cable to withstand greater external force. In addition, bio-based degradable polyester fiber is added, which is a polyester fiber prepared from renewable biomass resources. Through its fibrous structure, it crisscrosses inside the material to form a tough and resilient network, so that the mechanical properties of the cable material are greatly improved, and the fatal defect of the traditional material that is easy to be brittle is completely compensated. By improving the internal structure of the new energy cable material, the strength and toughness of the subsequent cable manufacturing are improved; 3. The present invention uses silane coupling agent to modify nano-silica, wherein the nano-silica has the characteristics of small size effect, surface effect, etc. After being modified by silane coupling agent, on the one hand, the surface activity is improved, the compatibility with the matrix resin and other additives is greatly improved, and it can be evenly dispersed in the material; on the other hand, it can fill the microscopic pores inside the material, reduce the porosity, reduce the risk of leakage, and cooperate with mica powder to further enhance the insulation performance, thereby providing a guarantee for the stable operation of the cable in a complex electrical environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flowchart of the preparation method of the highly flame-retardant new energy cable material of the present invention; Figure 2 The present invention is a flowchart of the modified preparation method of modified ammonium polyphosphate. DETAILED DESCRIPTION
[0022] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Comparative Example Refer to the current production standard of national standard GB / T5023-2008, and select and prepare production materials in accordance with this implementation standard. Example
[0024] A highly flame-retardant new energy cable material and a preparation method thereof, wherein the new energy cable material is made of the following raw materials by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of modified ammonium polyphosphate, 13 parts of melamine cyanurate, 8 parts of nano-montmorillonite, 9 parts of mica powder, 6 parts of silane coupling agent-modified nano-silica, 4 parts of bio-based degradable polyester fiber, and 10 parts of auxiliary additives; The preparation method of new energy cable materials is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry.
[0025] 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed.
[0026] 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating to ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, plasticize the polyvinyl chloride and ethylene-vinyl acetate copolymer for 5 to 8 minutes until they are melted and softened to form the base material raw material of the new energy cable material.
[0027] 4) Then, add nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives into the internal mixer in order. Then, adjust the temperature of the internal mixer to 130-150°C and continue mixing for 20-30 minutes to form a masterbatch of new energy cable materials.
[0028] 5) Adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally kneaded mixture.
[0029] 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained. Example
[0030] A highly flame-retardant new energy cable material and a preparation method thereof, wherein the new energy cable material is made of the following raw materials by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 13 parts of modified ammonium polyphosphate, 8 parts of melamine cyanurate, 6 parts of nano-montmorillonite, 9 parts of mica powder, 6 parts of silane coupling agent-modified nano-silica, 4 parts of bio-based degradable polyester fiber, and 10 parts of auxiliary additives; The preparation method of new energy cable materials is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry.
[0031] 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed.
[0032] 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating to ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, plasticize the polyvinyl chloride and ethylene-vinyl acetate copolymer for 5 to 8 minutes until they are melted and softened to form the base material raw material of the new energy cable material.
[0033] 4) Then, add nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives into the internal mixer in order. Then, adjust the temperature of the internal mixer to 130-150°C and continue mixing for 20-30 minutes to form a masterbatch of new energy cable materials.
[0034] 5) Adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally kneaded mixture.
[0035] 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained. Example
[0036] A highly flame-retardant new energy cable material and a preparation method thereof, wherein the new energy cable material is made of the following raw materials by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of modified ammonium polyphosphate, 13 parts of melamine cyanurate, 4 parts of nano-montmorillonite, 9 parts of mica powder, 6 parts of silane coupling agent-modified nano-silica, 2 parts of bio-based degradable polyester fiber, and 10 parts of auxiliary additives; The preparation method of new energy cable materials is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry.
[0037] 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed.
[0038] 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating to ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, plasticize the polyvinyl chloride and ethylene-vinyl acetate copolymer for 5 to 8 minutes until they are melted and softened to form the base material raw material of the new energy cable material.
[0039] 4) Then, add nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives into the internal mixer in order. Then, adjust the temperature of the internal mixer to 130-150°C and continue mixing for 20-30 minutes to form a masterbatch of new energy cable materials.
[0040] 5) Adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally kneaded mixture.
[0041] 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained. Example
[0042] A highly flame-retardant new energy cable material and a preparation method thereof, wherein the new energy cable material is made of the following raw materials by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of modified ammonium polyphosphate, 13 parts of melamine cyanurate, 8 parts of nano-montmorillonite, 9 parts of mica powder, 3 parts of silane coupling agent-modified nano-silica, 4 parts of bio-based degradable polyester fiber, and 10 parts of auxiliary additives; The preparation method of new energy cable materials is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry.
[0043] 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed.
[0044] 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating to ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, plasticize the polyvinyl chloride and ethylene-vinyl acetate copolymer for 5 to 8 minutes until they are melted and softened to form the base material raw material of the new energy cable material.
[0045] 4) Then, add nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives into the internal mixer in order. Then, adjust the temperature of the internal mixer to 130-150°C and continue mixing for 20-30 minutes to form a masterbatch of new energy cable materials.
[0046] 5) Adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally kneaded mixture.
[0047] 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained. Example
[0048] A highly flame-retardant new energy cable material and a preparation method thereof, wherein the new energy cable material is made of the following raw materials by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of modified ammonium polyphosphate, 13 parts of melamine cyanurate, 8 parts of nano-montmorillonite, 5 parts of mica powder, 6 parts of silane coupling agent-modified nano-silica, 4 parts of bio-based degradable polyester fiber, and 6 parts of auxiliary additives; The preparation method of new energy cable materials is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry.
[0049] 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed.
[0050] 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating to ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, plasticize the polyvinyl chloride and ethylene-vinyl acetate copolymer for 5 to 8 minutes until they are melted and softened to form the base material raw material of the new energy cable material.
[0051] 4) Then, add nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives into the internal mixer in order. Then, adjust the temperature of the internal mixer to 130-150°C and continue mixing for 20-30 minutes to form a masterbatch of new energy cable materials.
[0052] 5) Adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally kneaded mixture.
[0053] 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained.
[0054] The performance test of new energy cable materials is carried out in accordance with the following reference standards: The limiting oxygen index is tested according to GB / T10707-2008: "Oxygen index method for determination of combustion performance of rubber"; Tensile strength: Conduct tensile test on cable material samples according to ASTMD638 standard; Resistivity refers to ASTMD257 standard, and a high-precision high resistance meter is used to apply DC voltage to the sample under a specific temperature and humidity environment to measure and calculate the volume resistivity value; The bending radius test refers to the IEC60811-503 standard. Use special tooling to wind the cable sample around a cylinder with a specified diameter, observe whether the surface is damaged, and determine the bending radius. The elongation at break is tested with reference to the determination method of elongation at break in Part 3 of NB / T20421.3-2017: Detection method of status of cables important to safety in nuclear power plants; The tensile strength retention rate after accelerated aging refers to the simulated aging conditions of the ASTM G154 standard. The sample is placed in an aging box and subjected to alternating cycles of ultraviolet light, high temperature, and high humidity for a specific length of time. Then, the tensile strength test is performed according to the ASTM D638 standard to obtain the retention rate.
[0055] Table 1 shows the key performance data of new energy cable materials: Among them, the value of the bending radius is a multiple of the cable diameter, and the actual maximum bending radius of the cable is calculated using the diameter and the multiple value. Through the display of Table 1, it can be clearly observed that Examples 1-5 have obvious performance improvements compared with the comparative examples, wherein Example 1 is the preferred raw material addition standard for adding the scheme, and Examples 2-5 are all reduced in the addition of various raw materials, thereby resulting in performance differences, wherein especially Example 5, in which the main polyvinyl chloride, ethylene-vinyl acetate copolymer, modified ammonium polyphosphate, melamine cyanurate, nano-montmorillonite, silane coupling agent modified nano-silica and bio-based degradable polyester fiber are all added and prepared according to Example 1, but because the auxiliary additives and mica powder therein are reduced in amount, and the plasticizer in the auxiliary additive can assist in improving the mechanical properties of the cable, the compatibilizer can better mix the above materials, significantly improving the compatibility and stability of the system, when the mixed cable materials are less compatible with each other, it will also cause a decrease in performance, and the mica powder can provide better insulation performance for the cable material.
[0056] Among them, Example 2 reduces the addition amount of modified ammonium polyphosphate, melamine cyanurate and nano-montmorillonite, and then compared with Example 1, the value of the limiting oxygen index thereof is significantly reduced, thereby confirming that the above materials play a strong role in improving the flame retardant effect in new energy cable materials; Among them, Example 3 is the reduction of nano-montmorillonite and bio-based degradable polyester fiber. Compared with Example 1, the tensile strength and bending radius of Example 3 are significantly reduced, so it is confirmed that the above materials have a good improvement effect on the strength and mechanical properties of new energy cable materials; Among them, Example 4 is a nano-silica modified by reducing the silane coupling agent. Compared with Example 1, the resistivity of Example 4 has an obvious downward trend, so it is confirmed that the above-mentioned material has an improving effect on the insulation performance of new energy cable materials.
[0057] Table 2 shows other performance test results of new energy cable materials: Among them, the elongation at break is the data of extending the cable rope until it breaks, which can confirm whether the cable is prone to breakage when laid, bent or pulled by external force. The tensile strength retention rate after accelerated aging for 1000 hours is an experiment in which the cable is accelerated aged for 1000 hours by physical means and then its tensile strength is tested again. It can be seen from Table 2 that in the two extension test items, Examples 1-5 have obvious improvements compared with the test results of the control example. Example
[0058] See also Figure 1-2This embodiment provides a highly flame-retardant new energy cable material. The new energy cable material includes the following component raw materials by weight: 100-130 parts of polyvinyl chloride, 30-40 parts of ethylene-vinyl acetate copolymer, 15-20 parts of modified ammonium polyphosphate, 10-15 parts of melamine cyanurate, 5-10 parts of nano-montmorillonite, 8-12 parts of mica powder, 5-8 parts of silane coupling agent modified nano-silica, 3-5 parts of bio-based degradable polyester fiber, and 5-15 parts of auxiliary additives.
[0059] The new energy cable material is made of the following components in parts by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of modified ammonium polyphosphate, 13 parts of melamine cyanurate, 8 parts of nano-montmorillonite, 9 parts of mica powder, 6 parts of silane coupling agent modified nano-silica, 4 parts of bio-based degradable polyester fiber, and 10 parts of auxiliary additives.
[0060] Mica powder is made of muscovite powder, which has excellent insulation properties and an inherent natural lamellar structure. A tight charge blocking network is carefully woven inside the material, so that the insulation resistance can be steadily increased. At the same time, the lamellar structure of mica powder can also enhance the mechanical properties of the material to a certain extent, playing a role similar to reinforcing fiber, improving the tensile strength and modulus of the material, so that it can better disperse stress when subjected to force and enhance the overall mechanical properties.
[0061] Modified ammonium polyphosphate is a mixture of melamine-formaldehyde resin, urea-formaldehyde resin and gelatin-arabic gum in a mass ratio of 5:3:2; Auxiliary additives include: plasticizers, compatibilizers, antioxidants and light stabilizers; Among them, the plasticizer is dioctyl phthalate, the compatibilizer is maleic anhydride grafted polyethylene, the antioxidant is hindered phenol antioxidant, which is a main antioxidant and can capture free radicals generated during the processing, storage and use of the material, interrupt the oxidation chain reaction, and inhibit the oxidative aging of the material from the source. The light stabilizer is a hindered amine light stabilizer. Outdoors or in a light environment, the hindered amine light stabilizer can absorb ultraviolet energy and release it in a harmless form, effectively preventing ultraviolet rays from damaging the molecular chains of the material, avoiding degradation, discoloration, and brittleness of the material due to photooxidation, and further ensuring the performance stability of the material under long-term lighting conditions.
[0062] The preparation method of modified ammonium polyphosphate is as follows: 1) Selecting ammonium polyphosphate particles as raw materials, and then preparing a corresponding amount of ethanol solution and a container, then adding the ammonium polyphosphate particles and the ethanol solution into the container, and simultaneously adding a dispersant, and then starting stirring to obtain an ammonium polyphosphate suspension; 2) Prepare another container, add melamine-formaldehyde resin, urea-formaldehyde resin and gelatin-arabic gum into the container, add a corresponding amount of clean water, start stirring until mixing is complete, and obtain a prepolymer solution; 3) Add the ammonium polyphosphate suspension to the prepolymer solution, stir and mix again, and allow the mixture to stand for reaction after the mixture is mixed. After the reaction is completed, filter, wash and dry the modified ammonium polyphosphate mixture to obtain modified ammonium polyphosphate particles.
[0063] The static reaction time after the ammonium polyphosphate suspension and the prepolymer solution are stirred and mixed is 5-10 hours. The modified ammonium polyphosphate mixed solution is dried by vacuum freeze drying. The pH value of the prepolymer solution is acidic, specifically 3-5. The preparation reaction temperature of the prepolymer solution is 60-85°C.
[0064] The preparation method of the highly flame-retardant new energy cable material is applied to the highly flame-retardant new energy cable material. The preparation method of the new energy cable material is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry.
[0065] 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed.
[0066] 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating to ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, plasticize the polyvinyl chloride and ethylene-vinyl acetate copolymer for 5 to 8 minutes until they are melted and softened to form the base material raw material of the new energy cable material.
[0067] 4) Then, add nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives into the internal mixer in order. Then, adjust the temperature of the internal mixer to 130-150°C and continue mixing for 20-30 minutes to form a masterbatch of new energy cable materials.
[0068] 5) Adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally kneaded mixture.
[0069] 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained.
[0070] The extruder is divided into three parts, namely zone one, zone two and zone three. The temperature settings of each zone of the extruder are: zone one 150-170℃, zone two 170-190℃, zone three 190-210℃. The speed of the extrusion screw in the extruder is 90-130rpm. The three zones of the extruder correspond to heating, melting and molding in the extrusion process, which can improve the quality of extrusion of new energy cable materials.
[0071] The pretreatment methods of polyvinyl chloride and ethylene-vinyl acetate copolymer are as follows: 1) Prepare a stainless steel container, pour polyvinyl chloride and ethylene-vinyl acetate copolymer into the stainless steel container, and spread the polyvinyl chloride and ethylene-vinyl acetate copolymer evenly; 2) Then put the stainless steel container containing polyvinyl chloride and ethylene-vinyl acetate copolymer into the vacuum oven, then start the vacuum oven, set the drying temperature to 40-60°C, and then perform vacuum extraction to reduce the vacuum degree in the vacuum oven to 0.09-0.1MPa, and the drying time is 3-5h; 3) After the vacuum drying of polyvinyl chloride and ethylene-vinyl acetate copolymer is completed, the vacuum oven is closed and nitrogen is filled into the vacuum oven until the pressure in the vacuum oven returns to normal pressure, and then the polyvinyl chloride and ethylene-vinyl acetate copolymer are taken out to complete the pretreatment of polyvinyl chloride and ethylene-vinyl acetate copolymer. By pretreating polyvinyl chloride and ethylene-vinyl acetate copolymer, it is found that there is moisture hidden in polyvinyl chloride and ethylene-vinyl acetate copolymer. In the subsequent processing, the moisture will be rapidly vaporized in the high temperature environment. The bubbles generated by vaporization will cause structural defects in the product, destroy the density and uniformity of the material, and then deteriorate the various performances of the product. Therefore, the moisture in polyvinyl chloride and ethylene-vinyl acetate copolymer is removed through this pretreatment method, thereby improving the performance and quality of new energy cable materials produced and processed by polyvinyl chloride and ethylene-vinyl acetate copolymer.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Highly flame-retardant new energy cable material, characterized in that: The new energy cable material includes the following component raw materials in parts by weight: 100-130 parts of polyvinyl chloride, 30-40 parts of ethylene-vinyl acetate copolymer, 15-20 parts of modified ammonium polyphosphate, 10-15 parts of melamine cyanurate, 5-10 parts of nano-montmorillonite, 8-12 parts of mica powder, 5-8 parts of silane coupling agent modified nano-silica, 3-5 parts of bio-based degradable polyester fiber, and 5-15 parts of auxiliary additives.
2. The highly flame-retardant new energy cable material according to claim 1, characterized in that: The new energy cable material is made of the following component raw materials in parts by weight: 110 parts of polyvinyl chloride, 35 parts of ethylene-vinyl acetate copolymer, 18 parts of modified ammonium polyphosphate, 13 parts of melamine cyanurate, 8 parts of nano-montmorillonite, 9 parts of mica powder, 6 parts of silane coupling agent modified nano-silica, 4 parts of bio-based degradable polyester fiber, and 10 parts of auxiliary additives.
3. The highly flame-retardant new energy cable material according to claim 1, characterized in that: The modified ammonium polyphosphate is prepared by mixing melamine-formaldehyde resin, urea-formaldehyde resin and gelatin-arabic gum in a mass ratio of 5:3:2; The auxiliary additives include: plasticizer, compatibilizer, antioxidant and light stabilizer; Wherein, the plasticizer is dioctyl phthalate, the compatibilizer is maleic anhydride grafted polyethylene, the antioxidant is a hindered phenol antioxidant, and the light stabilizer is a hindered amine light stabilizer.
4. The highly flame-retardant new energy cable material according to claim 1, characterized in that: The preparation method of the modified ammonium polyphosphate is as follows: 1) Selecting ammonium polyphosphate particles as raw materials, and then preparing a corresponding amount of ethanol solution and a container, then adding the ammonium polyphosphate particles and the ethanol solution into the container, and simultaneously adding a dispersant, and then starting stirring to obtain an ammonium polyphosphate suspension; 2) Prepare another container, add melamine-formaldehyde resin, urea-formaldehyde resin and gelatin-arabic gum into the container, add a corresponding amount of clean water, start stirring until mixing is complete, and obtain a prepolymer solution; 3) Add the ammonium polyphosphate suspension to the prepolymer solution, stir and mix again, and allow the mixture to stand for reaction after the mixture is mixed. After the reaction is completed, filter, wash and dry the modified ammonium polyphosphate mixture to obtain modified ammonium polyphosphate particles.
5. The highly flame-retardant new energy cable material according to claim 4, characterized in that: The static reaction time of the ammonium polyphosphate suspension and the prepolymer solution after stirring and mixing is 5-10 hours, and the modified ammonium polyphosphate mixed solution is dried by vacuum freeze drying.
6. The highly flame-retardant new energy cable material according to claim 4, characterized in that: The pH value of the prepolymer solution is acidic, specifically 3-5, and the preparation reaction temperature of the prepolymer solution is 60-85°C.
7. The method for preparing a highly flame-retardant new energy cable material is applied to the highly flame-retardant new energy cable material as claimed in any one of claims 1 to 6, characterized in that: The preparation method of the new energy cable material is as follows: 1) Place the nano-montmorillonite in a high-speed mixer, add corresponding amounts of dispersant and water, then turn on the mixer, and continue to rotate and stir the high-speed mixer at 1500-2000 rpm for 30-45 minutes to obtain a nano-montmorillonite slurry; 2) Weigh a corresponding amount of silane coupling agent-modified nano-silica, pour it into a corresponding amount of anhydrous ethanol, and then place the mixed solution in an ultrasonic disperser for 30 to 45 minutes of ultrasonic dispersion treatment until a uniform and stable dispersion is formed; 3) Weigh the corresponding amount of polyvinyl chloride and ethylene-vinyl acetate copolymer for pretreatment, put the pretreated polyvinyl chloride and ethylene-vinyl acetate copolymer into the internal mixer steadily, then turn on the internal mixer for heating, and ensure that the internal temperature of the internal mixer is controlled at 120-140°C. Under this temperature condition, perform plasticizing operation on polyvinyl chloride and ethylene-vinyl acetate copolymer for 5-8 minutes until they are melted and softened to form the base material raw material of new energy cable materials; 4) Then, nano-montmorillonite, modified ammonium polyphosphate, melamine cyanurate and auxiliary additives are added to the internal mixer in order, and then the temperature of the internal mixer is adjusted to 130-150°C, and the mixing is continued for 20-30 minutes to form a masterbatch of new energy cable materials; 5) adding mica powder, bio-based degradable polyester fiber and the silane coupling agent modified nano-silica dispersion prepared in 2) to the prepared masterbatch, adjusting the temperature of the internal mixer to 140-160° C. again, and continuing to mix for 15-20 minutes within this temperature range to obtain an internally mixed mixture; 6) The internally kneaded mixture is slowly pushed into the single-screw extruder, and the internally kneaded mixture is extruded from the extruder. After the material is extruded, it is immediately cooled by air cooling. Subsequently, the extruded material is cooled, pulled, cut and granulated, and finally a finished new energy cable material is obtained.
8. The method for preparing a highly flame-retardant new energy cable material according to claim 7, characterized in that: The extruder is divided into three parts, namely zone one, zone two and zone three. The temperature settings of each zone of the extruder are: zone one 150-170°C, zone two 170-190°C, zone three 190-210°C.
9. The method for preparing a highly flame-retardant new energy cable material according to claim 7, characterized in that: The extrusion screw speed in the extruder is 90-130 rpm.
10. The method for preparing a highly flame-retardant new energy cable material according to claim 7, characterized in that: The pretreatment method of the polyvinyl chloride and ethylene-vinyl acetate copolymer is as follows: 1) Prepare a stainless steel container, pour polyvinyl chloride and ethylene-vinyl acetate copolymer into the stainless steel container, and spread the polyvinyl chloride and ethylene-vinyl acetate copolymer evenly; 2) Then put the stainless steel container containing polyvinyl chloride and ethylene-vinyl acetate copolymer into the vacuum oven, then start the vacuum oven, set the drying temperature to 40-60°C, and then perform vacuum extraction to reduce the vacuum degree in the vacuum oven to 0.09-0.1MPa, and the drying time is 3-5h; 3) After the vacuum drying of polyvinyl chloride and ethylene-vinyl acetate copolymer is completed, the vacuum oven is closed and nitrogen is filled into the vacuum oven until the pressure in the vacuum oven returns to normal pressure, and then the polyvinyl chloride and ethylene-vinyl acetate copolymer are taken out to complete the pretreatment of polyvinyl chloride and ethylene-vinyl acetate copolymer.
Citation Information
Cited By
Multi-synergistic enhanced polyurea elastomer material as well as preparation method and application thereof
CN121293722A